Platelets from Bleeding Simmental Cattle Have a Long Delay in both ADP-activated Expression of GpllB-IIIA Receptors and Fibrinogen-dependent Platelet Aggregation - Frojmovic, Mony M; Wong, Truman; Searcy, Gene P (Thrombosis and Haemostasis, 1996)
We have previously reported that platelets from bleeding Simmental cattle do not aggregate in vitro in response to ADP, collagen and calcium ionophore A23187, though calcium mobilization and myosin light chain phosphorylation do occur. The aggregation abnormality, measured by aggregometry, was ascribed to abnormal cytoskeletal expression, with the maximal numbers of activated GpIIb-IIIa receptors per platelet no different from that seen in normal bovine platelets activated with ADP. We have therefore sought to compare the kinetics of microaggregation with the rate of expression of GpIIb-IIIa receptors required for mediating fibrinogen (Fg)-dependent platelet aggregation, to provide a more direct molecular explanation for the aggregation abnormality. We compared aggregation kinetics of ADP-activated platelets using both aggregometry and particle counting to monitor microaggregation. Fibrinogen receptor expression was monitored with FITC-labelled human Fg and with the reporting antibody for activated GpIIb-IIIa, FITC-PAC1, using flow cytometry. The affected platelets show a marked delay in onset of microaggregation for ADP-activated platelets stirred with human Fg, paralleded by an unusual delay in activated GpIIb-IIIa receptor expression (DARE) for otherwise competent Fg binding. The on-rates for Fg binding to platelets maximally pre-activat-ed with PMA are identical for normal and affected platelets, whether comparing the binding of human or bovine Fg. The unique DARE syndrome explains the observed delay in aggregation of platelets from affected Simmental cattle and predicts the bleeding problems due to delayed binding of adhesive proteins.